2004
DOI: 10.1177/014556130408301219
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman Disease with Extranodal Manifestation in the Head

Abstract: The term sinus histiocytosis with massive lyrnphadenopathy (SHML) was introduc ed by Rosai and Dorfinan in 1969. Although SHML was initially described as low-pain cerv ical lymphadenopathy accompanied by fevet; leukocy tosis, an increased erythrocyte sedim entation rate, and hypergammaglobulinemia, extranodal involvement is observed in 25 to 40% of cases. This pathology is velY rare and involvement of the nasal fossae and paranasal sinus es is exceptional. We present two atypical cases of extranodal involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The abnormal soft tissue generally shows associated contrast enhancement and may show increased activity on PET [5,[18][19][20][21][22][23][24]. On MRI, sinus lesions may also show marked hypointensity on T2-weighted imaging [19].…”
Section: Sinus Histiocytosis With Massive Lymphadenopathymentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal soft tissue generally shows associated contrast enhancement and may show increased activity on PET [5,[18][19][20][21][22][23][24]. On MRI, sinus lesions may also show marked hypointensity on T2-weighted imaging [19].…”
Section: Sinus Histiocytosis With Massive Lymphadenopathymentioning
confidence: 99%
“…Orbital involvement is most commonly unilateral [2,6]. Imaging findings include extraconal soft-tissue masses with proptosis (most common); infiltration of the eyelids, extraocular muscles, and fat; lacrimal gland involvement; and rarely, involvement of the globe [5,6,18,22,[29][30][31][32][33][34][35]. Ischemia of the globe can also occur [30].…”
Section: Sinus Histiocytosis With Massive Lymphadenopathymentioning
confidence: 99%
“…The background typically shows lymphocytes, plasma cells, and occasional neutrophils. 2,11 Extra nodal involvement is seen in 40 per cent of RDD cases which show similar morphological features to its nodal counterpart, although fewer histiocytes with emperipolesis are encountered. 2,12 The internalised lymphocytes are usually located within cytoplasmic vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…Extranodal involvement is seen in 40 per cent of RDD cases, which show similar morphological features to its nodal counterpart, although fewer histiocytes with emperipolesis are encountered. 2 Literature reviews show that up until 2004 about 600 cases of RDD had been reported, in all races but mainly in Caucasians (43 per cent), in any age group, but mainly in first and second decades (81 per cent), and more in males than females (2:1). 3 The most common presenting symptom of this disease is painless bilateral cervical lymphadenopathy which is seen in 90 per cent of the patients, and in 43 per cent of the cases the patients have at least one site of extra-nodal involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Pustular, psoriasiform, and acneiform presentations have also been documented. [3][4][5] The cutaneous RDD has a benign course usually with spontaneous regression in most cases.…”
Section: Methodsmentioning
confidence: 99%